2002
DOI: 10.1080/030097402760375197
|View full text |Cite
|
Sign up to set email alerts
|

Knee joint synovitis in Sjo¨gren's syndrome. Sonographic study

Abstract: Ultrasound detects effusion and synovial proliferation caused by synovitis. The study was undertaken to evaluate the signs of synovitis in patients with primary Sjögren's Syndrome (SS). Joint effusion was detected and synovial thickness was measured in the suprapatellar synovial bursa. Results have been compared with those obtained by sonographic assessment of knee joint in patients with secondary SS and RA. with secondary SS and connective tissue diseases, with RA, and in healthy subjects. Synovial thickening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The role of US in SLE has been reported by two studies which show the high frequency of subclinical joint involvement [54,55]. Also preliminary studies on the evaluation of knee and hands in Sjögren syndrome gave promising results [56,57]. Finally, MSUS, by enabling visualization of muscle fibre fine details and the presence of interstitial edema, can disclose the typical inflammation signs of myositis, even if with less sensitivity than MRI, and guide the needle for muscular biopsy [58][59][60].…”
Section: The Omeract Special Interest Group On Us Ismentioning
confidence: 89%
“…The role of US in SLE has been reported by two studies which show the high frequency of subclinical joint involvement [54,55]. Also preliminary studies on the evaluation of knee and hands in Sjögren syndrome gave promising results [56,57]. Finally, MSUS, by enabling visualization of muscle fibre fine details and the presence of interstitial edema, can disclose the typical inflammation signs of myositis, even if with less sensitivity than MRI, and guide the needle for muscular biopsy [58][59][60].…”
Section: The Omeract Special Interest Group On Us Ismentioning
confidence: 89%
“…The US analysis reliably detects both abnormalities and it is thus considered an accurate imaging method for the study of synovitis [19,[27][28][29]. Previous studies demonstrated that magnetic resonance analysis of a single sagittal slice and US measurements of synovial thickness in the suprapatellar bursa are reliable and accurate methods for the quantification of the severity of the inflammatory process in RA and in Sj6gren's syndrome patients [19,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies [19], thickness of the synovial membrane was considered abnormal when higher than 3 ram. Joint effusion, secondary to synovitis, was diagnosed when hypoanechoic fluid collection was shown within the articular space [19,25]. Finally, the presence of Baker's cyst was ascertained when fluid distension of the gastrocnemiosemimembranous bursa was demonstrated.…”
Section: Clinical Evaluationmentioning
confidence: 99%
See 2 more Smart Citations